‘It’s not because we don’t believe in it...’: Headteachers’ perceptions of implementing physically active lessons in school - Skage, Ingrid (BMC Public Health, 2019)
INTRODUCTION: Implementation of school-based physical activity (PA) programmes has proven to be difficult, particularly due to schools’ focus on academic performance and lack of organisational support for PA interventions. However, physically active lessons (PA integrated into academic lessons) holds promise as a teaching method that increases children’s PA levels without reducing academic time. Headteachers play a significant role in facilitating change in school, but little is known about headteachers’ attitudes towards physically active lessons and their benefits. The purpose of this study was to explore headteachers’ perceptions of physically active lessons, and identify factors affecting headteachers’ acceptance or rejection of physically active lessons implementation. METHOD: A total of 29 semi-structured telephone interviews were conducted with headteachers in primary and secondary schools in the city of Stavanger, Norway. Adopting a phenomenological approach, qualitative data were analysed using inductive content analysis. RESULTS: Although most of the headteachers believed that physically active lessons could contribute positively to pupils’ health and learning, only four of 29 schools decided to proceed with implementation. Physically active lessons were more likely to be adopted when the intervention addressed a clearly defined priority area at the school. Change overload and lack of in-depth knowledge of physically active lessons’ function and intent appeared to be the most important factors for choosing not to implement physically active lessons. CONCLUSION: One of the major challenges for headteachers was deciding which of the many proposed changes the school should prioritise. If physically active lessons was to be prioritised by headteachers it is very important to communicate thoroughly to the headteachers what the schools can achieve by implementing physically active lessons and how the innovation aligns with school policies and goals. Given the flexibility inherent in physically active lessons and the schools’ differing needs and priorities, it was important to emphasise to headteachers that physically active lessons could be adapted to different local school contexts.